Not bitten by Ixodes ticks or bitten without symptoms, why still to worry? - Andreychyn, Mykhaylo; Shkilna, Maria; Tokarskyy, Oleksandr; Ivakhiv, Oleh; Smahlii, Zoriana; Korda, Mykhaylo (Central European journal of public health, 2024)
OBJECTIVES: The purpose of the current study was to analyse the risks of Lyme borreliosis (LB) among 1,070 forestry workers, the influence of responsible behaviour (use of repellents, skin self-inspection) on Borrelia screening result status, and the occurrence of immediate and mid-term symptoms after tick bites and LB positive serological screening test. METHODS: The questionnaire was conducted as well as blood tests for LB disease by one-stage serological screening procedure using ELISA for specific B. burgdorferi IgM and IgG antibodies (EuroImmun AG company, Germany). RESULTS: While 39.6% of foresters were LB positive among bitten foresters, as many as 27.0% were LB positive among those, who did not recall any tick attacks at all. Individuals with known history of tick bites had significantly higher odds (1.770×) of being LB positive (p < 0.05), while the use of repellents or skin self-inspection after visiting woods had no influence on LB results. The odds of skin discolouration after tick bites was significantly lower (0.682×) in case of LB positive test compared to LB negative test (p < 0.05), which can be explained by the fact that foresters could be unaware about erythema migrans appearance and timing, considering tick bite and developed later rash as completely separate events. Moreover, 69.1% of the bitten foresters with LB positive result developed no secondary symptoms (excluding those related to the skin), and the most frequent clinical symptoms were arthralgia (24.9%), followed by myalgia (7.6%), headache (5.7%), and damage to facial nerve (2.7%), which are non-specific and can be present in other illnesses. CONCLUSION: Therefore, the recommendations proposed would be the regular laboratory testing for LB of sensitive and at-risk population, who visits endemic woody areas, irrespective of all other factors involved.
Keywords: lesnictví; Surveys and Questionnaires; Borrelia burgdorferi; Ixodes; risk; Humans; lidé středního věku; Lyme Disease; lymeská nemoc; Female; Aged; dospělí; klíště; ELISA; senioři; lidé; zvířata; Germany; Enzyme-Linked Immunosorbent Assay; průzkumy a dotazníky; Německo; Adult; foresters; kousnutí klíštětem; ženské pohlaví; Male; Middle Aged; Forestry; Lyme borreliosis; Animals; Tick Bites; mužské pohlaví